Annealing Treatment: A Facile Approach to Enhance Transfer Kinetics for a LiFePO4/C Cathode. Issue 10 (6th September 2022) - Yang, Maoping; Jia, Xueying; Li, Pengfei; Yao, Jie; Wang, Weiwei
Abstract: Nowadays, solid phase synthesis has been proven to be the most cost‐effective and convenient approach to mass preparation of a LiFePO4 /C cathode. Nevertheless, the LiFePO4 /C cathode usually shows unsatisfactory electrochemical performance due to its high proportion of antisite defects and inefficient carbon coating. In this work, a post‐synthesis annealing treatment method is used to improve the ionic and electron transfer kinetics of high‐temperature solid phase synthesized LiFePO4 /C. Owing to the annealing treatment, the proportion of Fe‐Li antisite defects in the LiFePO4 crystal can be significantly reduced. The graphitization degree of carbon coating on LiFePO4 has been increased. This contributes to the enhancement of rapid transfer kinetics and suppressed polarization of the electrode. Abstract : In order to overcome the sluggish transfer kinetics of a LiFePO4 /C cathode, a post‐synthesis annealing treatment method is proposed to reduce the concentration of antisite defects and electrode polarization of the LiFePO4 /C composite. The graphitization degree of carbon coating on LiFePO4 has been increased. This composite cathode presents enhanced electrochemical performance.